Analysis of Population Growth Trends Based on Geographic Information Systems in East Jakarta - Aryaguna, Prama Ardha (Faculty of Geography, Universitas Gadjah Mada, 2025)
The increase in population is accompanied by equal distribution. In this context, population density of Jakarta is partly due to urbanization and long-term settlement. Therefore, this research is carried out to identify sub-districts experiencing the fastest population growth and the accommodated capacity. Population issues must be a central point of sustainable development allowing every resident and future generations to live healthily, prosperously, productively, and harmoniously with the environment. The relationship between population growth rate (PGR) and spatial aspects such as healthcare facilities, trade facilities, transportation facilities, government offices, education facilities, industry, and the availability of residential buildings from 2017 to 2022 is determined through Geographic Information System (GIS)-based analysis using statistical methods. The trend of PGR in East Jakarta sub-districts is high in the northwest and north, bordering Central and North Jakarta. Meanwhile, spatial aspects influencing high population growth are the availability of residential buildings and schools. Increased residential buildings and public schools in a sub-district due to the zoning policy in student enrollment are directly proportional to population growth.Received: 2024-07-27 Revised: 2024-10-18 Accepted: 2025-01-30 Published: 2025-02-12